Philanthropic Landmarks: The Toronto Trail from a Comparative Perspective, 1870s to the 1930s - Adam, Thomas (Urban History Review / Revue d'histoire urbaine, 2001)
In this essay the author compares nineteenth-and early twentieth-century philanthropy in Toronto to that in German and American cities such as Leipzig and New York, The argument is divided into four parts, each dealing with different aspects of philanthropy. In the first part of this essay, the author develops his concept of "philanthropic culture", which is the theoretical basis for this essay. The main thesis is that donating became a bourgeois behavioural pattern, which served to integrate new elites, women, and religious and ethnic minorities into social structures, mainly "High Society". The second part of the essay examines wealthy Torontonians who became philanthropists. This part paints the portrait of the typical Toronto philanthropist. The concept of philanthropy did not emerge on the American continent, but was imported from Europe. Therefore, the third part of the essay is dedicated to exploration of how philanthropic models were transferred from Europe to Toronto. The last part investigates the development of Toronto's philanthropic landmarks—the Toronto General Hospital, the Art Gallery of Toronto, the Royal Ontario Museum, and the Toronto Housing Company.